Comparison of typical and atypical computed tomography patterns regarding reversibility and fibrosis in pulmonary sarcoidosis - Susam, Seher (Ann Thorac Med, 2021)
PURPOSE: This study aims to investigate whether there is a significant difference between typical and atypical parenchymal patterns in the development of fibrosis, which is the most crucial factor affecting morbidity in pulmonary sarcoidosis. METHODS: In our hospital, 145 cases with Siltzbach Types 2 and 3 sarcoidoses diagnosed by clinical, radiological, and histopathologic were retrospectively investigated. Perilymphatic nodules, accompanying mosaic attenuation, and interlobular septal thickening and central peribronchovascular bunch-like thickening on high-resolution computed tomography were assessed as typical. Solid nodules, galaxy finding, consolidation, ground-glass opacity, isolated mosaic attenuation, and interlobular septal thickening, and pleural fluid were accepted as atypical findings. Findings indicating fibrosis were fine and rough reticular opacity, traction bronchiectasis, volume loss, and cystic changes. For the analysis of variables, SPSS 25.0 program was used. RESULTS: Ten (16%) of the 61 cases with typical findings and 16 (19%) of the 84 with atypical findings developed fibrosis (P = 0.827). The mean age of cases with fibrosis was higher. With the cut-off of 50 years, sensitivity was 61.5%, and specificity was 68.9%. The highest fibrosis rate was in cases with ground glass pattern (n = 7/17), whereas higher reversibility rates were in those with miliary pattern (n = 9/12) and galaxy sign (n = 5/6). CONCLUSION: The incidence of fibrosis is higher in the atypical group with no significant difference. The incidence of fibrosis differs in each atypical pattern, being highest in ground-glass opacity and lowest in the miliary pattern.